KEWAJIBAN, LARANGAN, DAN SANKSI HUKUM TERHADAP PASIEN DALAM SISTEM HUKUM KESEHATAN INDONESIA: ANALISIS YURIDIS NORMATIF ATAS REGULASI KEJUJURAN INFORMASI MEDIS - Gautama, Elly Christanty; Vitrianingsih, Yeni; Sirenden, Monita Tinting; Mardikaningsih, Rahayu; Issalillah, Fayola (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study aims to analyze the regulation of legal obligations, prohibitions, and sanctions against patients in the Indonesian health legal system through a normative juridical approach. The main sources of analysis consist of Law Number 17 of 2023 concerning Health, Government Regulation Number 28 of 2024, and Minister of Health Regulation Number 4 of 2018. The results of the study show that patients have a strategic position as legal subjects who are required to provide honest and complete health information. This is in line with the main goal of providing effective, safe, and professional health services. In a positive legal framework, dishonesty or falsification of information by patients in general has not been threatened with sanctions in general, except for the prevention of infectious disease outbreaks that have a wide impact on public health. In these special situations, the patient's dishonesty can be qualified as an act of obstructing government efforts and can be subject to administrative and criminal sanctions with fines of up to Rp500,000,000, as regulated in the Health Law. This study suggests the need to increase legal education in the community, strengthen regulatory supervision, and protect patients' rights so that the application of legal norms does not cause inefficiencies or inequality in legal protection. The implications of this regulation contribute to the creation of health services that are more transparent, responsible, and support the state's efforts to optimally protect public health.